Decision Making in the Innovation Process: Data-Driven vs. Data-Informed - Muge Abac (Journal of Innovation in Polytechnic Education)
There has been a growing trend in the use of data-related buzzwords, and “data-driven decision-making” is one of them. This buzzword is often confused with “data-informed decision-making,” emphasizing the need to understand the role of data for effective decision-making. The article explains this misconception through tables and insights from experts like Geoffrey Moore, Tendayi Viki and Alexander Osterwalder. It emphasizes the need for a balanced approach, using both qualitative and quantitative data, and suggests starting with qualitative insights before moving to quantitative analysis. Ultimately, it stresses the importance of aligning organizational structures to leverage data effectively for innovation.